Optimizing the Use of Online Single Submission to Accelerate Business Licensing for Micro Enterprises - Sang Ayu Putu Rahayu; Dina Silvia Puteri (Universitas Negeri Semarang, 2024)
This study explores the optimization of the Online Single Submission (OSS) system, specifically the Risk-Based Approach (RBA), to accelerate business licensing for micro, small, and medium enterprises (MSMEs) in Kebojongan Village, which is home to various small businesses in the fields of convection, food production, bakery, and more. In order to operate legally, these businesses require several permits, such as the Business Identification Number (NIB), which can be processed through the OSS RBA system. However, many MSME owners in Kebojongan Village lack knowledge regarding the importance and ease of registering for business permits, which hinders the formalization and growth of their businesses. The research aims to address this issue by increasing community awareness and skills related to the OSS system, thereby simplifying the business licensing process and fostering economic development in the village. With the NIB, MSMEs can easily obtain other essential permits, including business legality certifications, Indonesian National Standards (SNI), and Halal Product Guarantee Certificates. The service activities include interviews, counseling, mentoring, and evaluations on the use of OSS RBA and NIB registration, focusing on overcoming challenges such as forgotten passwords or registration errors. This service intervention aims to improve the adoption of the OSS system, enabling MSMEs in Kebojongan Village to complete the necessary licensing process with ease, supporting their growth and contributing to local economic development. By enhancing understanding and accessibility of the OSS platform, this initiative hopes to facilitate the accelerated development of business licensing for micro-enterprises in Kebojongan Village.